Role of Interface(s) for the Growth of Ultra‐Thin Amorphous Oxides on Al–Si Alloys: A Thermodynamic Analysis. Issue 2 (11th January 2014) - Panda, Emila; Manwani, Krishna
Abstract : This study presents a thermodynamic analysis to predict the type of initial, amorphous oxide overgrowth (i.e., am ‐Al2 O3 or am ‐SiO2 ) on bare Al–Si alloy substrates. This analysis have taken into account the energies associated with both its interfaces (interface between the Al–Si alloy substrate and the thin oxide film and interface between the thin oxide film and vacuum) along with the bulk Gibbs free energy of oxide formation. This developed analysis is then applied for various parameters, such as, Si alloying element content at the substrate/oxide interface, the growth temperature, the oxide film thickness (up to 1 nm), and various low‐index crystallographic surfaces of the substrate. It is found that am ‐SiO2 overgrowth is thermodynamically preferred for a combination of lower oxide film thickness, lower growth temperature, and lower Si alloying content at the alloy/oxide interface. This is because of the overcompensation of the lower energies of both the interfaces over the bulk Gibbs free energy. Furthermore, it is found that for all cases, am ‐Al2 O3 forms a more stable interface with Al–Si alloy than am ‐SiO2.